Effect of glenoid concavity loss on shoulder stability- a case report in a professional wrestler. Issue 1 (December 2016) - Moroder, Philipp; Haniel, Franziska; Quirchmayr, Michael; Schulz, Eva; Eppel, Manfred; Matis, Nicholas; Auffarth, Alexander; Resch, Herbert
Abstract Background Current glenoid defect measurement techniques only quantify bone loss in terms of defect diameter or surface. However, the glenoid depth plays an important role in shoulder stabilization by means of concavity compression. Case presentation We present a case of a professional wrestler who suffered from anterior shoulder instability after sustaining a bony Bankart lesion without loss of glenoid surface area but flattening of the concavity due to medialization of the fragment. The patient's glenoid concavity was reconstructed arthroscopically by reduction and percutaneous screw fixation of the bony fragment along with a capsulo-ligamentous shift. Changes of the glenoid concavity with according alterations in the Bony Shoulder Stability Ratio (BSSR) were analyzed on pre-op, post-op, and follow-up CT scans. Postoperative CT scans revealed a deepened concavity (3.3 mm) and improved BSSR (46.1 %) compared to pre-op scans (0.7 mm; 11.3 %). Follow-up CT scans showed a slight remodeling of the glenoid concavity (3.2 mm) with steady BSSR (44.7 %). Conclusion This case shows that the passive stabilizing effect of the glenoid can be compromised by loss of concavity despite the absence of loss of articular surface. Therefore, addressing the concavity loss and resulting reduction of the BSSR is recommended in these cases. Bony Bankart repair was successful in restoring the BSSR of the patients shoulder as determined by mathematical calculations based on CT scans.